Ectopic Expression of Rv0023 Mediates Isoniazid/Ethionamide Tolerance via Altering NADH/NAD+ Levels in Mycobacterium smegmatis - Gupta, Shailesh Kumar; Angara, Rajendra Kumar; Yousuf, Suhail; Reddy, Chilakala Gangi; Ranjan, Akash (Frontiers in Microbiology, 2020)
Tuberculosis (TB) caused by Mycobacterium tuberculosis (Mtb) accounts for nearly 1.2 million deaths per annum worldwide. Due to the emergence of multidrug resistance (MDR) Mtb strain, tuberculosis, an otherwise, curable and avertable disease still remains as one of the leading causes of morbidity and mortality. Isoniazid (INH) forms the first line of anti-TB drug while Ethionamide (ETH) is used as the second line of anti-TB drug. INH and ETH resistance develop through a network of genes involved in various biosynthetic pathways. In this study, we identified Rv0023, an Mtb protein belonging to the XRE family of transcription regulators, which has a role in generating higher tolerance towards INH and ETH in Mycobacterium smegmatis (Msmeg). Overexpression of Rv0023 in Msmeg leads to the development of INH and ETH tolerant strains. The strains expressing Rv0023 have a higher ratio of NADH/NAD+, and this physiological event is known to play a crucial role in the development of INH/ETH co-resistance in Msmeg. Gene expression analysis of some target genes revealed reduction in the expression of ndh gene, but no direct interaction was observed between the Rv0023 and ndh promoter region. Rv0023 is divergently expressed to Rv0022 ( whiB5) and we observed direct interaction of recombinant Rv0023 protein with the upstream region of Rv0022 and this was confirmed using reporter constructs in Msmeg. However, we found no indication that this interaction might play a role in the development of INH/ETH drug tolerance.